Reduction of open space in Urban planning : a case study of Osmani Udyan - Bhuiyan, Mohammad Saiful Islam (BRAC University, 2013)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2010.